Population dynamics of an invasive forest insect and associated natural enemies in the aftermath of invasion: implications for biological control. Issue 5 (22nd July 2015) - Duan, Jian J.; Bauer, Leah S.; Abell, Kristopher J.; Ulyshen, Michael D.; Van Driesche, Roy G.; Sheppard, Andy
Summary Understanding the population dynamics of exotic pests and associated natural enemies is important in developing sound management strategies in invaded forest ecosystems. The emerald ash borer (EAB) Agrilus planipennis Fairmaire is an invasive phloem‐feeding beetle that has killed tens of millions of ash Fraxinus trees in North America since first detected in 2002. We evaluated populations of immature EAB life stages and associated natural enemies over a 7‐year period (2008–2014) in six stands of eastern deciduous forest in southern Michigan, where Tetrastichus planipennisi Yang and two other Asian‐origin EAB parasitoids were released for biological control between 2007 and 2010. We observed ≈90% decline in densities of live EAB larvae in infested ash trees at both parasitoid‐release and control plots from 2009 to 2014 and found no significant differences in EAB density or mortality rates by parasitoids, avian predators or other undetermined factors between parasitoid‐release and control plots. The decline in EAB larval density in our study sites was correlated with significant increases in EAB larval parasitism, first by native parasitoids, then by T. planipennisi. Life table analyses further indicated that parasitism by the introduced biocontrol agent and the North American native parasitoids contributed significantly to the reduction of net EAB population growth rates in our study sites from 2010 to 2014. Synthesis and applications. Our findings indicate that successful biocontrol of emerald ash borer (EAB) may involve suppression of EAB abundance both by local, generalist natural enemies (such as Atanycolus spp.) and by introduced specialist parasitoids (such as T. planipennisi). Biological control programmes against EAB in the aftermath of invasion should focus on establishing stable populations of T. planipennisi and other introduced specialist parasitoids for sustained suppression of low‐density EAB populations. Moreover, we recommend releasing the introduced specialist biocontrol agents as soon as possible to prevent the outbreak of EAB populations in both newly infested and aftermath forests when EAB densities are still low.